Cover Picture: Advancing knowledge of gas migration and fugitive gas from energy wells in northeast British Columbia, Canada (Greenhouse Gas Sci Technol 2/2019). Issue 2 (9th April 2019) - Cahill, Aaron G.; Beckie, Roger; Ladd, Bethany; Sandl, Elyse; Goetz, Maximillian; Chao, Jessie; Soares, Julia; Manning, Cara; Chopra, Chitra; Finke, Niko; Hawthorne, Iain; Black, Andrew; et al.
Abstract : The cover image is based on the In the Field article Advancing knowledge of gas migration and fugitive gas from energy wells in northeast British Columbia, Canada by Aaron G. Cahill et al., DOI:10.1002/ghg.1856 . Image Credit: Dr. Aaron Graham Cahill, University of British Columbia.